SPECIFICITY OF INNOVATIVE PROJECT MANAGEMENT OF SMALL AND MEDIUM BUSINESSES - Tatiana E. Platonova; Tamara A. Bystrova (Статистика и экономика, 2016)
Issues of investing small businesses, results and problems of small enterprises in Russia in recent years are considered in the article. The main components of the establishment and operation of venture capital firms and their importance in achieving effective results in the implementation of innovative projects are analyzed. Areas of success of small businesses in innovation sphere are identified.